Space weather with an arc’s ∼2 h trip across the nightside polar cap - Lyons, Larry R.; Nishimura, Yukitoshi; Liu, Jiang; Yadav, Sneha; Zou, Ying; Bristow, William A.; Donovan, Eric; Nishitani, Nozomu (Frontiers in Astronomy and Space Sciences, 2024)
Flow channels can extend across the polar cap from the dayside to the nightside auroral oval, where they lead to localized reconnection and auroral oval disturbances. Such flow channels can persist within the polar cap >1½ hours, can move azimuthally with direction controlled by IMF By, and may affect time and location of auroral oval disturbances. We have followed a polar cap arc as it moved duskward from Canada to Alaska for ~2 hr while connected to the oval. Twodimensional ionospheric flows show an adjacent flow channel that moved westward with the arc and was a distinct feature of polar cap convection that locally impinged upon the outer boundary of the auroral oval. The flow channel's interaction with the oval appears to have triggered two separate substorms during its trip across western Canada and Alaska, controlling the onset location and contributing to subsequent development of substorm activity within the oval. The first substorm (over Canada) occurred during approximately equatorward polar cap flow, whereas the second substorm (over Alaska) occurred as the polar cap arc and flow channel bent strongly azimuthally and appeared to 'lay down" along the poleward boundary. The oval became unusually thin, leading to near contact between the polar cap arc and the brightening onset auroral arc within the oval. These observations illustrate the crucial role of polar cap flow channels in the time, location, and duration of space weather activity, and the importance of the duration and azimuthal motion of flow channels within the nightside polar cap.